Organizational management of communication in Social Responsibility: an indicator of media literacy in managers - Barrientos Báez, Almudena; Gonzálvez Vallés, Juan Enrique; Caldevilla-Domínguez, David (Revista Venezolana de Gerencia, 2023)
The research analyzes the interactions of users with regard to content administrated and published by Spain’s Government to promote media literacy and combat misinformation, and its implications for similar actions in the management of organizations which might be tasked with these very mission. To meet this objective, all the tweets issued by the official profile of this institution (4938) were collected and those that dealt with any of the following categories were selected: COVID-19, Restrictions, Vaccines, and Fake News. An analysis of the descriptive statistics of the possible interactions on Twitter was carried out, that is likes, comments and retweets. Similarly, an analysis of the means of the variances was carried out to observe if there were significant differences between and within the groups. The content generated is shared more because it is a public institution of reference, but to a much lesser extent in the case of fake news. Even more illuminating is the mostly negative feeling generated in the comments.